(untitled) (Sociologisk Forskning, 2015)
Contentment in the moment ”Contentment in the moment” is a classic grounded theory exploring safety and contentment within a small community in northern Norway. The purpose of the study was to explore the village’s everyday life from a participant’s perspective and to develop an understanding of their living conditions. We found different survival strategies, which have their roots in the village’s history of poverty, isolation and harsh climate. Today these strategies have changed from a matter of life and death to a modern psychosocial foundation of contentment. The study is based on four and a half years of observations, in-depth interviews and informal but focused conversations with people living in Polarfjorden. The data was analysed using the constant comparative method of classic grounded theory. In this article we further relate our work to more general sociological theory, more specifically to Charles Tilly’s work on reason and routines.